Recent Progress in Rice–Xanthomonas oryzae Interactions - Yuting Qi; Qiong Rao; Chenglong Lu; Junyi Gong; Yuxuan Hou (Biology, 2025)
Rice bacterial blight (BB) and bacterial leaf streak (BLS), caused by Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas oryzae pv. oryzicola (Xoc), respectively, are among the most devastating bacterial diseases threatening global rice production. The interactions between rice and Xanthomonas oryzae are complex and dynamic, involving recognition, attack, defense, and adaptation mechanisms enacted by both the rice host and the pathogens. This review summarizes recent advances in understanding rice–Xanthomonas oryzae interactions, focusing on infection models, pathogenic mechanisms, and immune responses elicited by Xanthomonas oryzae. Special attention is devoted to the roles of transcription activator-like effectors (TALEs) and non-TALE effectors in pathogenicity, the functions of resistance (R) genes in defense, and the interconnected molecular networks of interactions derived from multi-omics approaches. Understanding these interactions is essential for developing effective disease-resistance strategies and creating elite disease-resistant rice varieties.